Toolpath Motion Strategy and Feed Rate in CNC Milling on Energy Consumption of Machining Process - Saputra, Luqman Dwi; Yudiyanto, Eko (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
The use of CNC milling machines to produce components, especially aluminum brackets used for automotive, is one of the advances in the industrial field. The use of CNC milling machines has the advantage of producing processes with speed accuracy, and better workpiece quality than conventional machines. This research investigates energy consumption in the CNC milling process by varying the toolpath motion strategies—Zigzag, Constant Overlap Spiral, Parallel Spiral, and Parallel Spiral Clean Corners—as well as feed rates of 700 mm/min, 800 mm/min, 900 mm/min, and 1000 mm/min. The goal is to find out the best parameters for using energy in the machining process. The material used in this research is Aluminum 6061. The shape tested is a bracket. The simulation was conducted to determine the machining process time using Mastercam software. The simulation results indicate that the Zigzag toolpath motion strategy at a feed rate of 1000 mm/min produces the lowest energy consumption (307.620 Kilojoules) whereas the Parallel Spiral Clean Corners toolpath at a feed rate of 700 mm/min produce the highest energy consumption (457.142 Kilojoules). The selection of appropriate machining parameters has a significant influence on the efficiency of processing time and production costs. By selecting the right toolpath motion strategy and feeding parameters, the manufacturing industry can increase productivity and reduce production costs more effectively.